Developing The Potential of Tourism Villages from The Perspective of Reinventing Government in Kesiman Kertalangu - Herminantoko, Antonius; Gunawan, Daniel Elfresh; Sembiring, Rachel Sepfanya; Runtulalo, Rio Maichel; Gracella, Sherryl; Puspita, Virta (Green Publisher Indonesia, 2025)
This study explores the development potential of tourism villages from the perspective of Reinventing Government in Kesiman Kertalangu, East Denpasar, Bali. The research highlights the importance of regional autonomy and community involvement in enhancing tourism sectors to improve local welfare. By applying the principles of Reinventing Government, the study aims to identify strategic approaches for optimizing tourism village potential, focusing on government innovation, community participation, and effective management practices. The research employs a qualitative descriptive method with a case study approach to analyze the implementation of Reinventing Government principles in Kesiman Kertalangu Tourism Village. Data were collected through interviews, observations, and document reviews to assess the alignment between government practices and entrepreneurial governance. Findings reveal that 9 out of 10 Reinventing Government principles are effectively implemented, including catalyst government, results-oriented governance, and decentralized government. However, the mission-driven government principle remains unfulfilled due to budget constraints. Key supporting factors include natural attractions and cultural uniqueness, while challenges involve inadequate human resources and limited funding. The study concludes that Reinventing Government principles significantly contribute to tourism village development, offering a model for other regions. Recommendations include improving budget flexibility and enhancing human resource capabilities to sustain growth. The research implications extend to policy-making, advocating for collaborative governance and community empowerment in tourism development.